The Magic Show Mystery - Warner, Gertrude Chandler; Nang Chan Yeema (Morton Grove, IL, United States Albert Whitman & Company, 1998)
After seeing a magician perform, Benny enlists his dog Watch to help him put on his own magic show, but then both Watch and Benny's magic bag disappear.
Keywords: Story Collection